Practice of Credit System for Goods Without Time Period According to Sharia Economic Law - Fitriana, Alvi Lailatuz Zahro; Fitria, Norma (al-Rasῑkh: Jurnal Hukum Islam, 2025)
Uncertainty in a transaction can be one of the factors leading to problems. Time is closely related to sales transactions using a credit system. If the payment period is not specified, it will certainly lead to ambiguity. This study aims to understand the practices and perspectives of Islamic economic law concerning the credit goods system without a specified deadline. The article employs a conceptual approach with a type of juristic-empirical research. The findings indicate that the credit goods system without a specified deadline implemented in Sambirejo village has become a solution for the community to meet their needs through weekly installment payments without a defined timeframe for payment. However, when analyzed through the lens of Islamic economic law theory, this practice may lead to losses due to buyers' negligence in making installment payments, sometimes even disappearing. Additionally, this practice does not align with the principles of justice and trust. The validity of the contract has not been achieved because it fails to meet the requirements for credit sales, and scholars assert that credit contracts containing ambiguity regarding the payment timeline are considered invalid. Therefore, this research is expected to provide a deeper understanding of the suitability of the credit goods system without a specified deadline as it exists in the field of Islamic economic law.